Seed germination, seedling emergence, and response to herbicides of wild bushbean (Macroptilium lathyroides) - Chauhan, Bhagirath S.; De Leon, Ma Jenina (Cambridge University Press, 2014)
Experiments were conducted in laboratory and screenhouse to determine the effects of light, temperature, salt and water stress, seed burial depth, and amount of rice residue on seed germination and seedling emergence of wild bushbean and to evaluate the response of that weed to commonly available POST herbicides in the Philippines. Germination (81 to 85%) was not influenced by light; however, it was higher at 30/20 C (88%) than at 25/15 C (82%) and 35/25 C (80%) day/night temperatures. The sodium chloride and osmotic potential required for 50% inhibition of maximum germination were 149 mM and −0.28 MPa, respectively. Seedling emergence (81%) was similar for seeds placed on the soil surface and for seeds buried up to 4 cm deep. No seedlings emerged from a burial depth of 8 cm. Rice residue applied on the soil surface up to 8 t ha−1did not affect seedling emergence (72 to 80%) of wild bushbean. The herbicide bentazon provided 100% control of wild bushbean when applied at the three- to five-leaf stages. However, to achieve 100% control by 2,4-D and metsulfuron-methyl + chlorimuron-ethyl, herbicides had to be applied at the three-leaf stage. The information gained from this study can help in developing components of integrated weed management programs for wild bushbean. A deep-tillage operation to bury weed seeds below their maximum depth of emergence and early application of an effective POST herbicide can help in managing this weed in rice fields.